Expropriation of minority interest via debt in family firms: evidence from Malaysia - Abdullah, Norhidayah (Faculty of Accountancy, 2011)
It is documented that there is a significant degree of separation between cash flow rights and control rights in corporations with concentrated ownership, where power lies in the hands of controlling shareholders, particularly in family firms. The presence of this separation contributes to agency problems between controlling shareholders and minority interests, potentially leading to the expropriation of minority interests. One method of such expropriation is via debt, as debt is a tool often utilized to expropriate minority interests. Thus, this study examines the relationship between the separation of cash flow rights and control rights and the debt policy of Malaysian listed family firms over the three-year period of 2006, 2007, and 2008. This relationship serves to indicate whether the expropriation of minority interests exists in Malaysian listed family firms. The present study reveals that the separation of cash flow rights and control rights is positively related to the debt ratio. However, this indicates that the separation of cash flow rights and control rights does not necessarily lead to an increase in debt policy among Malaysian listed family firms. Ultimately, the results are not conclusive due to the non-significant relationship and data limitations; thus, evidence regarding the expropriation of minority interests in Malaysian listed family firms cannot be generalized.